Evaluation of the effectiveness of an intervention in a health team to prevent falls in hospitalized elderly people - Cunha, Luís Filipe Correia da (2021)
To evaluate the effectiveness of an intervention program in practices and behaviors of a health team to prevent falls in hos pitalized elderly people. Method: This was an action, mixed-methods, and longitudinal study that applied an intervention based on TeamSTEPPS® , and organized into five domains: team training, communication, leadership, monitoring, and mutual support. The population was nurses and nursing aides who worked at the medical service of a Portuguese hospital center. Data were obtained by consulting process records and interviews, and by applying the Scale of Practices and Behaviors of Teams for Fall Prevention. Results: There was improvement in all indicators of the scale, with evident progress in discussion of risk factors and preventive measures to be implemented. Conclusion: This intervention promoted decision-making regarding the preventive measures to be applied to each elderly person and improved communication and the interest in identifying the causes of falls to prevent their recurrence.